Process characteristics of surface finishing using viscoelastic abrasive laden media on industrial metals in non-contact ultrasonic finishing process - Chien Artadi, Myron Huihao (2019)
Ultrasonic machining is a non-conventional machining technique used to process hard and brittle materials. It provides improved surface finishing, provides better strength and fatigue life of the processed product. With the assistance of ultrasonic vibrations, it uses a low viscous media abrasive slurry to fracture and impact the working surface. To prove the success of ultrasonic machining, this project will explore the feasibility and effectiveness of viscoelastic media abrasive slurry which is commonly used in abrasive flow machining on a non-contact ultrasonic finishing process setup. Three different industrial metals were machined using wire-cut electric discharge machining and tested. A comprehensive study has been done with variating amplitudes and machining time intervals to investigate the changes in surface roughness, material removal, 3D surface topography and microscopic imaging.